Chemical exchange rotation transfer imaging of phosphocreatine in muscle. (7th December 2020) - Zu, Zhongliang; Lin, Eugene C.; Louie, Elizabeth A.; Jiang, Xiaoyu; Lankford, Christopher L.; Damon, Bruce; Does, Mark D.; Gore, John C.; Gochberg, Daniel F.
Abstract : In chemical exchange saturation transfer (CEST) imaging, the signal at 2.6 ppm from the water resonance in muscle has been assigned to phosphocreatine (PCr). However, this signal has limited specificity for PCr since the signal is also sensitive to exchange with protein and macromolecular protons when using some conventional quantification methods, and will vary with changes in the water longitudinal relaxation rate. Correcting for these effects while maintaining reasonable acquisition times is challenging. As an alternative approach to overcome these problems, here we evaluate chemical exchange rotation transfer (CERT) imaging of PCr in muscle at 9.4 T. Specifically, the CERT metric, AREXdouble, cpw at 2.6 ppm, was measured in solutions containing the main muscle metabolites, in tissue homogenates with controlled PCr content, and in vivo in rat leg muscles. PCr dominates CERT metrics around 2.6 ppm (although with nontrivial confounding baseline contributions), indicating that CERT is well‐suited to PCr specific imaging, and has the added benefit of requiring a relatively small number of acquisitions. Abstract : Chemical exchange saturation transfer (CEST) signals at 2 and 2.6 ppm were assigned to creatine (Cr) and phosphocreatine (PCr), respectively. However, conventional asymmetric analysis causes contaminations in the quantification of these two CEST signals (A). Here, we applied our previously developed chemical exchange rotation transfer (CERT) to provide more specific quantification of these two CEST signals (B).